2011
DOI: 10.1143/apex.4.022601
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensing with Up-Converting Submicron-Sized LiNbO3:Er3+/Yb3+Particles

Abstract: We present the temperature dependence of the green up-converted luminescence in submicron-sized LiNbO 3 :Er 3þ /Yb 3þ particles in the range between 12 and 180 C. It is shown that LiNbO 3 :Er 3þ /Yb 3þ exhibits a very high sensitivity (S ¼ 0:007/ C at physiological temperature and a maximum value of S ¼ 0:014/ C at 350 C) that surpasses those previously found for other materials based on Er 3þ /Yb 3þ luminescence, indicating that LiNbO 3 :Er 3þ /Yb 3þ is a suitable probe for optical temperature sensing through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(73 citation statements)
references
References 40 publications
7
65
0
1
Order By: Relevance
“…For example, Yang et al reported that in La 2 (WO 4 ) 3 host the C value is 18.1 [24], while Rai and Swart et al found that, in SrWO 4 host, the C value is as high as 21.1 [21]. The highest C value reported so far is about 32, appeared in the submicron-sized LiNbO 3 particles prepared by Cantelar et al [25]. However, owing to the high mismatch in ionic radius and valence, LiNbO 3 can accommodate merely lowconcentration doping of RE ions, therefore cannot yield bright upconversion emission.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Yang et al reported that in La 2 (WO 4 ) 3 host the C value is 18.1 [24], while Rai and Swart et al found that, in SrWO 4 host, the C value is as high as 21.1 [21]. The highest C value reported so far is about 32, appeared in the submicron-sized LiNbO 3 particles prepared by Cantelar et al [25]. However, owing to the high mismatch in ionic radius and valence, LiNbO 3 can accommodate merely lowconcentration doping of RE ions, therefore cannot yield bright upconversion emission.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] UC refers to an anti-Stokes type nonlinear optical emission process in which one higher energy photon is emitted for every two or more absorbed lower energy photons. 10 Since the first experimental demonstration in 1966, 11 this effect has received renewed interest due to its ever expanding application base in, for example, lasing, 12 laser cooling, 13 temperature sensing, 14 biomedical imaging and therapy, 15,16 3D displays, 17 and, more recently, for broadening the spectral response of PV devices. [4][5][6][7][8][9] In the context of Si PV devices, the UC of the sub-bandgap photons (k > 1100 nm) into above-bandgap photons (k < 1100 nm) increases the theoretical efficiency limit of a single-junction Si solar cell from near 30% up to 40% when illuminated under non-concentrated light.…”
Section: Introductionmentioning
confidence: 99%
“…Such kind of differences have been previously observed in other sub-micron sized particles and they can be attributed to a heating effect due to the presence of the IR-pumping beam [35]. In particular, it has been recently proved that this effect is useful to estimate the local temperature of the sample [36]. Following these calculations, the differences observed in the relative intensities are consistent with a local temperature, just in the excitation disk, of around 326 K. The power dependence of the most intense emission bands has also been explored; the results are presented in a logarithmic plot in Fig.…”
Section: Spectroscopic Characterizationmentioning
confidence: 60%